Interpretive hiking of orchids and bromeliads in Tepexilotla, Chocamán, Veracruz - Baltazar Bernal, Obdulia; Zavala Ruiz Jesús; Solís Zanotelli Flor Yarumi; Pérez Sato Juan Antonio; Sánchez Eugenio Octavio (Revista Mexicana de Ciencias Agrícolas, 2018)
The rural community of Tepexilotla, in the municipality of Chocamán, Veracruz, Mexico, is nestled in an area of cloud forest (BMM) and in order to exploit the high biodiversity of this ecosystem, by exploiting an Interpretive hiking that promotes education, conservation of biodiversity in the BMM and economic development of the community, this paper proposes a nature trail aimed for educating visitors to explore a path focused on species of wild orchids and bromeliads, attractive plants for their beauty and economic value, in order to reduce illegal logging. This proposal is the result of participatory workshops, interviews and tours within the forest for selecting sites and identify species. Integrating eight points located on the banks of the Metlac River and has a distance of 4.4 km, which are traversed in a time of 4:30. During the tour, visitors can see 19 species of wild orchids, 5 bromeliads and other scenic and wildlife attractions. Apparently, the path has a high acceptance among the locals and are willing to participate as guides and allocate a percentage for the trail’s maintenance.